Konsep, Strategi Dan lmplementasi Managemen Energi Pada Sebuah Industri - Dako, Amarudin Y. (Jurnal Pelangi Ilmu, 2009)
This article aim to give understanding for the importance of management energy as ane optimal way of usage of energy resource later on can lessen oparating cost an industry. In its implemantation, managemen energy requires commitment from all levels in organization of business causing earns regular and is directional Technique outline managemen energy discaussed in this article can be application at corparate world without reference to measure or business type.